Health and safety Issues in exercise, wellness and sports for special people (2012)
People with special needs often have a combination of health problems, which are often tied to physical inactivity. Recent studies have looked at the heart and lung function of people with special needs, that when they are in their 20s, they often have the heart and lung function of people who are 20-30 years older (Adams, 2010). Inactivity and lack of exercise can make a person more likely to develop problems with the heart and blood vessels. Inactivity can also decrease a person's ability to take care of himself or herself. Anyone with special needs is likely to be less active and therefore at greater risk of having diseases such as obesity, Type 2 diabetes, high blood pressure and coronary heart disease. The importance of exercise and sporting activities to people with special needs cannot be overemphasized. A person who is active feels better about himself or herself. Physical activity in people with special needs can help improve their health, physical functions, self esteem and behaviour. It can help to support families and caregivers. This article outlines the benefits of exercise and sporting activities for people with special needs and ways to adapt various activities to meet special needs. This paper also expresses how exercise and sporting activities can help special needs people to develop a well- rounded exercise routine that includes aerobic activity, strength training, and stretching exercises, ways by which exercises and sports activities can be used to cure some of the diseases mentioned above, it is recommended that sports clinics and tournaments be organized to show case disability sports and deliver health related messages to individuals with special needs.